2018
DOI: 10.3892/ol.2018.7863
|View full text |Cite
|
Sign up to set email alerts
|

miR-145 suppresses the proliferation, invasion and migration of NSCLC cells by regulating the BAX/BCL-2 ratio and the caspase-3 cascade

Abstract: Although microRNA (miR)-145 has been identified to be a tumor suppressor in various types of tumor, it promotes the progression of non-small cell lung cancer (NSCLC). However, the precise underlying molecular mechanism of its action remains unclear. The present study investigated the effects of miR-145 on the proliferation, invasion, metastasis and apoptosis of the NSCLC A549 cell line and the underlying molecular mechanism of its action. In vitro cell proliferation, invasion, migration and apoptosis assays we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 44 publications
1
40
0
Order By: Relevance
“…Thus, the BAX/BCL‐2 ratio is a key regulator of apoptosis in lung cancer . Furthermore, caspase‐3, a member of the cysteine protease family, catalyzes crucial steps in apoptotic cell death . In this study, SCU increased the BAX/BCL‐2 ratio and the amount of cleaved caspase‐3 in A549 cells.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Thus, the BAX/BCL‐2 ratio is a key regulator of apoptosis in lung cancer . Furthermore, caspase‐3, a member of the cysteine protease family, catalyzes crucial steps in apoptotic cell death . In this study, SCU increased the BAX/BCL‐2 ratio and the amount of cleaved caspase‐3 in A549 cells.…”
Section: Discussionmentioning
confidence: 48%
“…Flow cytometry was used to externalize phosphatidylserine (cell surface changes) in A549 cells and our results show that the percentage of apoptotic cells is markedly increased in a concentration‐dependent manner. Decreasing the level of the anti‐apoptotic BCL‐2 protein and/or increasing the level of the pro‐apoptotic BAX protein plays an important role in disrupting mitochondrial homeostasis, which can lead to apoptotic cell death . Thus, the BAX/BCL‐2 ratio is a key regulator of apoptosis in lung cancer .…”
Section: Discussionmentioning
confidence: 99%
“…DPP8 upregulates the number of early apoptotic cells by interacting with Bcl‐2/Bax. As a key effector in cellular apoptosis, the B‐cell lymphoma 2 gene can block the apoptosis of some cells, such as lymphocytes, lung cancer cells and breast cancer cells . BCL‐2‐associated X protein can promote apoptosis and is a member of the Bcl‐2 gene family.…”
Section: Discussionmentioning
confidence: 99%
“…(Figure f). And high Bax / Bcl ‐ 2 ratio is related to cell apoptosis (Pan et al, ). All these quantitative assays of ΔΨm value, caspase‐3 activity and mRNA expression of apoptosis‐related genes indicated that cell apoptosis could be induced by the overexpression of MTSP3141 or MTSP3141△TP in FHM cells.…”
Section: Resultsmentioning
confidence: 99%